2006
DOI: 10.1093/humrep/del173
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of luteal-phase GnRH agonist administration on embryo implantation after ICSI in both GnRH agonist- and antagonist-treated ovarian stimulation cycles

Abstract: Luteal-phase GnRH agonist administration enhances ICSI clinical outcomes after GnRH agonist- and GnRH antagonist-treated ovarian stimulation cycles, possibly by a combination of effects on the embryo and the corpus luteum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
141
4
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(164 citation statements)
references
References 27 publications
10
141
4
9
Order By: Relevance
“…A natural cycle was chosen based on the previous study demonstrating higher ongoing pregnancy rate following the transfer of frozen-thawed embryos in natural cycles with spontaneous LH rise compared with natural cycles controlled by hCG for final oocyte maturation [12]; the administration of hCG injection on day of transfer was chosen based on the ability of hCG to further improve the function of the corpus luteum [13]; and the administration of GnRH-agonist relied on the previous observed higher pregnancy rate in patients who received a mid-luteal injection of a GnRH-agonist [14,15]. These latter effects were explained by a putative direct or indirect effect of the GnRH direct effect on the endometrium and/or corpus luteum.…”
Section: Discussionmentioning
confidence: 99%
“…A natural cycle was chosen based on the previous study demonstrating higher ongoing pregnancy rate following the transfer of frozen-thawed embryos in natural cycles with spontaneous LH rise compared with natural cycles controlled by hCG for final oocyte maturation [12]; the administration of hCG injection on day of transfer was chosen based on the ability of hCG to further improve the function of the corpus luteum [13]; and the administration of GnRH-agonist relied on the previous observed higher pregnancy rate in patients who received a mid-luteal injection of a GnRH-agonist [14,15]. These latter effects were explained by a putative direct or indirect effect of the GnRH direct effect on the endometrium and/or corpus luteum.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a recent meta analysis comparing outcomes between antagonist and agonist cycles, including 13 randomized clinical trials with a range of 2-101 pregnant cases for each study, miscarriage rates were not found to be different (11.7% vs 11.5%) [18]. However, the studies in this meta analysis in the Cochrane review did not take into account the plurality of gestations and the definitions of miscarriage were not uniform [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Short Communicationmentioning
confidence: 83%
“…Possibly an endometrial impact could be attributed to this result. In this regard, some investigators also used GnRH agonist following embryo transfer after the administration of GnRH antagonists in ovarian stimulation phase in order to increase pregnancy rates [14].…”
Section: Short Communicationmentioning
confidence: 99%
“…Well-designed randomized clinical studies are required to clarify any effect of luteal GnRH agonist addition on pregnancy outcome measures with different doses, timing, and administration routes of GnRH agonists. (J Turk Ger Gynecol Assoc 2015; 16: 96-101) Keywords: GnRH agonist, luteal phase support, in vitro fertilization (IVF), progesterone Received: 23 February, 2015 Accepted: 06 April, 2015 Addition of gonadotropin releasing hormone agonist for luteal phase support in in-vitro fertilization: an analysis of 2739 cycles Abstract secretion were some of the proposed potential mechanisms of actions (13,14). The purpose of this study was to evaluate whether the addition of single-dose GnRH agonist to the progesterone for luteal support in IVF cycles improves the pregnancy outcome measures, particularly the live birth rates.…”
Section: Discussionmentioning
confidence: 99%